RELATIONSHIP OF ATTITUDES AND PERCEPTIONS WITH ADHERENCE IN TREATMENT OF PULMONARY TUBERCULOSIS PATIENTS IN MEDAN, INDONESIA - Wahyuni, Arlinda Sari; Soeroso, Noni Novisari; Wahyuni, Dian Dwi; Amelia, Rina; Alona, Ivana (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â  Â Objective: This study aimed to analyze the relationship of attitudes and perceptions about tuberculosis (TB) with adherence to the treatment of TB patients in Medan. Methods: A quantitative cross-sectional design. The target population was all patients who admitted to seven primary health centers (PHCs) in Medan. Samples were new TB patients aged >18 years old, with the result of acid-fast bacilli (+) (n=100). Assessment of behavioral adherence, attitudes, and perceptions of treatment were done based on treatment behavior instruments that had been validated and analyzed by the Chi-square test and logistic regression. Results: The results showed that 55% of the patients adhered to their medication. There was a relationship between attitude and adherence of TB treatment (p<0.05). However, there is no wrong perception correlation with treatment adherence (p>0.05). A good attitude increased 3.7 (95% confidence interval 1624; 8549) times for adherence to TB treatment. Conclusions: The positive attitude of the TB patients improved TB treatment behavior. Structured education provided by doctors and TB officers in PHC should be done to improve the knowledge and attitude of TB patients.